2017
DOI: 10.1021/jacs.6b12174
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Surface-Immobilized Enzyme that Retains High Levels of Catalytic Activity in Air

Abstract: In the absence of aqueous buffer, most enzymes retain little or no activity; however, "water-free" enzymes would have many diverse applications. Here, we describe the chemically precise immobilization of an enzyme on an engineered surface designed to support catalytic activity in air at ambient humidity. Covalent immobilization of haloalkane dehalogenase on a surface support displaying poly(sorbitol methacrylate) chains resulted in ∼40-fold increase in activity over lyophilized enzyme powders for the gas-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…To investigate whether the GO sheets stabilize the CALB structure by preserving water molecules or by directly interacting with the CALB, we applied the thermogravimetric analysis (TGA) to determine the water contents of the lyophilized LGA, CALB and GO, respectively. We determined the mass loss of the bounded water molecules by incubating these materials at 110 °C for 30 min 37 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether the GO sheets stabilize the CALB structure by preserving water molecules or by directly interacting with the CALB, we applied the thermogravimetric analysis (TGA) to determine the water contents of the lyophilized LGA, CALB and GO, respectively. We determined the mass loss of the bounded water molecules by incubating these materials at 110 °C for 30 min 37 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Efforts have been made to rationally tailor the stability 33 , activity-pH profiles 34 , substrate affinity 35 , and reaction specificity of enzymes in aqueous phase 36 . A very recent gas-phase example by Badieyan et al 37 suggested that a hydrophilic microenvironment created by polymer network can preserve the activity of enzymes in a water-free condition. Compared with the lyophilized enzyme, they found that haloalkane dehalogenase immobilized on the surface of glass beads displaying poly(sorbitol methacrylate) could result in a 40-fold increase in activity at A w = 0.5.…”
Section: Introductionmentioning
confidence: 99%
“…Sum frequency generation vibrational spectroscopy (SFG-VS) has been demonstrated to be a powerful technique for investigating the interfacial structures and interactions at the molecular level . In previous studies, frequency-scanning SFG system has been effectively employed to investigate the static structure of proteins and peptides at different interfaces [4,5,7,8,25]. Despite many progresses, frequency-scanning SFG system takes more than ten minutes to acquire one spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…For the most sensitive enzymes, immobilization, encapsulation, or cross‐linking may help preserve activity under mechanical stress. Interestingly, immobilization has been demonstrated to increase the stability of haloalkane dehalogenase specifically under gas‐phase conditions . Further studies looking at improving protein stability in the context of mechanoenzymology are warranted to improve yields and facilitate enzyme recycling.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly,i mmobilization has been demonstrated to increaset he stability of haloalkaned ehalogenase specifically under gas-phase conditions. [160] Further studies lookinga ti mproving protein stabilityi nt he context of mechanoenzymology are warranted to improvey ields and facilitate enzyme recycling. The mechanical forces enabling mechanoenzymatic transformations have so far included batch processes in shakero r planetary mills, and continuous or batch extrusion.…”
Section: Discussionmentioning
confidence: 99%